Multi-dimensional impacts of Coronavirus disease 2019 pandemic on Sustainable Development Goal achievement - Angkana Lekagul; Anamika Chattong; Putthipanya Rueangsom; Orratai Waleewong; Viroj Tangcharoensathien (BMC, 2022)
Abstract Background Health, social and economic crises triggered by the Coronavirus disease pandemic (COVID-19) can derail progress and achievement of the Sustainable Development Goals. This commentary analyses the complex nexus of multi-dimensional impacts of the pandemic on people, prosperity, planet, partnership and peace. From our analysis, we generate a causal loop diagram explaining these complex pathways and proposed policy recommendations. Main text Health systems, health and wellbeing of people are directly affected by the pandemic, while impacts on prosperity, education, food security and environment are indirect consequences from pandemic containment, notably social measures, business and school closures and international travel restrictions. The magnitude of impacts is determined by the level of prior vulnerability and inequity in the society, and the effectiveness and timeliness of comprehensive pandemic responses. Conclusions To exit the acute phase of the pandemic, equitable access to COVID-19 vaccines by all countries and continued high coverage of face masks and hand hygiene are critical entry points. During recovery, governments should strengthen preparedness based on the One Health approach, rebuild resilient health systems and an equitable society, ensure universal health coverage and social protection mechanisms for all. Governments should review progress and challenges from the pandemic and sustain a commitment to implementing the Sustainable Development Goals.